Deutschsprachige Literatur(en) seit 1989

Bewegungswahrnehmung in Abhängigkeit von motorischer Expertise: Neurophysiologische Evidenz - Koester, Dirk; Güldenpenning, Iris; Schack, Thomas (Sportpsychologische Kompetenz und Verantwortung: 44. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Studierende schieben Pflichten auf, aber auch persönliche Projekte - Grund, Axel; Schmid, Sebastian; Klingsieck, Katrin B.; Fries, Stefan (Zeitschrift für Entwicklungspsychologie und Pädagogische Psychologie)
Die Forschung zum Thema Prokrastination betrachtet fast ausschließlich das Aufschieben von Handlungen, die als fremdbestimmte Verpflichtungen und Leistungshandlungen wahrgenommen werden und die zugunsten von attraktiveren Handlungsalternativen zurückgestellt werden. Am Beispiel der Alltagshandlungen Studierender wurde untersucht, inwieweit dieses Begriffsverständnis bestimmte phänomenologische Facetten vernachlässigt. 398 Studierende beschrieben aufgeschobene und stattdessen ausgeführte Alltagshandlungen einer konkreten Aufschiebeepisode anhand von 35 Merkmalen. Anschließend wurde mit Analysen latenter Profile überprüft, inwieweit sich typische Handlungsprofile unterscheiden und interpretieren lassen. Es konnten je drei distinkte Typen aufgeschobener und ausgeführter Handlungen identifiziert werden. Erstere lassen sich anhand ihrer wahrgenommenen Merkmalsprofile als Pflichthandlungen, persönliche Projekte und Aktivhandlungen beschreiben; letztere als Entspannungshandlungen, Sozialhandlungen und wiederum Pflichthandlungen. Die Profile von persönlichen Projekten und Aktivhandlungen zeigen, dass das Spektrum von aufgeschobenen Handlungen breiter ist, als in der Forschung zumeist vorausgesetzt wird. Vor dem Hintergrund dieser Befunde wird dafür argumentiert, die Konzeption und Erfassung von Prokrastination auf selbstbestimmte Handlungen und Aktivhandlungen zu erweitern.

Procrastination in a distance university setting - Klingsieck, Katrin B.; Fries, Stefan; Horz, Claudia; Hofer, Manfred (Distance Education)

Allgemeine Prokrastination: Entwicklung und Validierung einer deutschsprachigen Kurzskala der General Procrastination Scale (Lay, 1986) - Klingsieck, Katrin B.; Fries, Stefan (Diagnostica)
In der vorliegenden Studie wurde anhand einer Übersetzung der General Procrastination Scale (GPS; Lay, 1986 ) eine deutschsprachige Kurzskala zur Erfassung von allgemeiner Prokrastination entwickelt und validiert. In drei Teilstudien wurden (sprachliche) Äquivalenz, Faktorenstruktur, Reliabilität und Validität untersucht. Die GPS erwies sich als sprachlich äquivalent zum englischen Original (Vorstudie, N = 38). Die Exploration der Faktorenstruktur (Studie I, N = 1 253) lieferte jedoch keine eindeutigen Hinweise auf die Eindimensionalität der GPS. Aufgrund dessen wurde eine eindimensionale Kurzskala (GPS-K) entwickelt und in der letzten Studie (Studie II, N = 218) validiert. Die interne Konsistenz (Studie I, II) sowie die Test-Retest Reliabilität (Studie II) der Kurzskala waren zufriedenstellend. Die konvergente und diskriminante Validität konnte in Bezug auf andere Persönlichkeitsmerkmale gezeigt werden. Anhand eines Verhaltensmaßes konnten weitere Hinweise für die Konstruktvalidität gesammelt werden. Mit der deutschen Übersetzung und Entwicklung der GPS-K liegt demnach ein ökonomisches sowie reliables und valides Instrumente zur Erfassung von allgemeiner Prokrastination vor.
Keywords: Clinical Psychology

Elektrophysiologische Korrelate der Wahrnehmung sportlicher Handlungen und die Rolle motorischer Expertise - Koester, Dirk; Güldenpenning, Iris; Schack, Thomas (Neuromotion - Aufmerksamkeit, Automatisierung, Adaption. 9. gemeinsames dvs-Symposium der Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft)

Die Rolle motorischer Expertise bei der Wahrnehmung komplexer Handlungen - Schack, Thomas; Güldenpenning, Iris; Koester, Dirk (Abstracts of the 54. Conference of Experimental Psychologists (TeaP 2012))

Priming of future states in complex motor skills - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias; Schack, Thomas (Experimental Psychology)

That’s how we roll - Learning the Kayak Roll improves the ability to mentally rotate objects - Güldenpenning, Iris; Spiegel, Marnie Ann; Schack, Thomas (Abstracts of the 54. Conference of Experimental Psychologists (TeaP 2012))

Unconscious processing of feint and non-feint actions - Güldenpenning, Iris; Braun, J.; Schack, T. (Kongress der Deutschen Gesellschaft für Psychologie (DGPs))

Zur Funktion motorischer Expertise in der Bewegungswahrnehmung: Eine EEG-Studie - Koester, D.; Güldenpenning, Iris; Schack, T. (48. Kongress der Deutschen Gesellschaft für Psychologie (DGPs))

Gesund und erfolgreich in Paderborn studieren (GriPs): Analyse studentischer Lebensstile - Brandl-Bredenbeck, Hans-Peter; Kämpfe, Astrid; Köster, Carolin (ForschungsForum Paderborn)

„Hol dir deinen beneFIT“ : Einführung eines Gesundheitspasses für Studierende an der Universität Paderborn. Dokumentation 17. bundesweiter Kongress Armut und Gesundheit: 9./10. März 2012 in Berlin. - Köster, Carolin; Brandl-Bredenbeck, Hans-Peter; Kämpfe, Astrid

Zur Funktion motorischer Expertisen in der Bewegungswahrnehmung: Eine EEG-Studie - Koester, Dirk; Güldenpenning, Iris; Schack, Thomas (Tagungsband des 48. Kongress der Deutschen Gesellschaft für Psychologie (DGPs))

Zur Funktion motorischer Expertise in der Bewegungswahrnehmung: Eine EEG-Studie - Koester, Dirk; Güldenpenning, Iris; Schack, Thomas (48. Kongress der Deutschen Gesellschaft für Psychologie (DGPs))

Unconscious processing of feint and non-feint actions - Güldenpenning, Iris; Braun, Jelena; Schack, Thomas (48. Kongress der Deutschen Gesellschaft für Psychologie (DGPS))

Convey Vector Personalities – FPGA Acceleration with an OpenMP-like Effort? - Meyer, Björn; Schumacher, Jörn; Plessl, Christian; Förstner, Jens (Proc. Int. Conf. on Field Programmable Logic and Applications (FPL))
Although the benefits of FPGAs for accelerating scientific codes are widely acknowledged, the use of FPGA accelerators in scientific computing is not widespread because reaping these benefits requires knowledge of hardware design methods and tools that is typically not available with domain scientists. A promising but hardly investigated approach is to develop tool flows that keep the common languages for scientific code (C,C++, and Fortran) and allow the developer to augment the source code with OpenMPlike directives for instructing the compiler which parts of the application shall be offloaded the FPGA accelerator. In this work we study whether the promise of effective FPGA acceleration with an OpenMP-like programming effort can actually be held. Our target system is the Convey HC-1 reconfigurable computer for which an OpenMP-like programming environment exists. As case study we use an application from computational nanophotonics. Our results show that a developer without previous FPGA experience could create an FPGA-accelerated application that is competitive to an optimized OpenMP-parallelized CPU version running on a two socket quad-core server. Finally, we discuss our experiences with this tool flow and the Convey HC-1 from a productivity and economic point of view.
Keywords: funding-upb-forschungspreis; funding-maxup; tet_topic_hpc

IMORC: An Infrastructure and Architecture Template for Implementing High-Performance Reconfigurable FPGA Accelerators - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Microprocessors and Microsystems)
Keywords: funding-altera

Eight Ways to put your FPGA on Fire – A Systematic Study of Heat Generators - Happe, Markus; Hangmann, Hendrik; Agne, Andreas; Plessl, Christian (Proceedings of the International Conference on Reconfigurable Computing and FPGAs (ReConFig))
Due to the continuously shrinking device structures and increasing densities of FPGAs, thermal aspects have become the new focus for many research projects over the last years. Most researchers rely on temperature simulations to evaluate their novel thermal management techniques. However, the accuracy of the simulations is to some extent questionable and they require a high computational effort if a detailed thermal model is used.For experimental evaluation of real-world temperature management methods, often synthetic heat sources are employed. Therefore, in this paper we investigated the question if we can create significant rises in temperature on modern FPGAs to enable future evaluation of thermal management techniques based on experiments in contrast to simulations. Therefore, we have developed eight different heat-generating cores that use different subsets of the FPGA resources. Our experimental results show that, according to the built-in thermal diode of our Xilinx Virtex-5 FPGA, we can increase the chip temperature by 134 degree C in less than 12 minutes by only utilizing about 21% of the slices.

Pragma based parallelization - Trading hardware efficiency for ease of use? - Kenter, Tobias; Plessl, Christian; Schmitz, Henning (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
One major obstacle for a wide spread FPGA usage in general-purpose computing is the development tool flow that requires much higher effort than for pure software solutions. Convey Computer promises a solution to this problem for their HC-1 platform, where the FPGAs are conﬁgured to run as a vector processor and the software source code can be annotated with pragmas that guide an automated vectorization process. We investigate this approach for a stereo matching algorithm that has abundant parallelism and a number of different computational patterns. We note that for this case study the automated vectorization in its current state doesn’t hold its productivity promise. However, we also show that using the Vector Personality can yield a signiﬁcant speedups compared to CPU implementations in two of three investigated phases of the algorithm. Those speedups don’t match custom FPGA implementations, but can come with much reduced development effort.

Hardware/Software Platform for Self-aware Compute Nodes - Happe, Markus; Agne, Andreas; Plessl, Christian; Platzner, Marco (Proceedings of the Workshop on Self-Awareness in Reconfigurable Computing Systems (SRCS))
Today's design and operation principles and methods do not scale well with future reconfigurable computing systems due to an increased complexity in system architectures and applications, run-time dynamics and corresponding requirements. Hence, novel design and operation principles and methods are needed that possibly break drastically with the static ones we have built into our systems and the fixed abstraction layers we have cherished over the last decades. Thus, we propose a HW/SW platform that collects and maintains information about its state and progress which enables the system to reason about its behavior (self-awareness) and utilizes its knowledge to effectively and autonomously adapt its behavior to changing requirements (self-expression).To enable self-awareness, our compute nodes collect information using a variety of sensors, i.e. performance counters and thermal diodes, and use internal self-awareness models that process these information. For self-awareness, on-line learning is crucial such that the node learns and continuously updates its models at run-time to react to changing conditions. To enable self-expression, we break with the classic design-time abstraction layers of hardware, operating system and software. In contrast, our system is able to vertically migrate functionalities between the layers at run-time to exploit trade-offs between abstraction and optimization.This paper presents a heterogeneous multi-core architecture, that enables self-awareness and self-expression, an operating system for our proposed hardware/software platform and a novel self-expression method.

Turning control flow graphs into function calls: Code generation for heterogeneous architectures - Barrio, Pablo; Carreras, Carlos; Sierra, Roberto; Kenter, Tobias; Plessl, Christian (Proceedings of the International Conference on High Performance Computing and Simulation (HPCS))
Heterogeneous machines are gaining momentum in the High Performance Computing field, due to the theoretical speedups and power consumption. In practice, while some applications meet the performance expectations, heterogeneous architectures still require a tremendous effort from the application developers. This work presents a code generation method to port codes into heterogeneous platforms, based on transformations of the control flow into function calls. The results show that the cost of the function-call mechanism is affordable for the tested HPC kernels. The complete toolchain, based on the LLVM compiler infrastructure, is fully automated once the sequential specification is provided.

Exploration of Ring Oscillator Design Space for Temperature Measurements on FPGAs - Rüthing, Christoph; Happe, Markus; Agne, Andreas; Plessl, Christian (Proceedings of the International Conference on Field Programmable Logic and Applications (FPL))
While numerous publications have presented ring oscillator designs for temperature measurements a detailed study of the ring oscillator's design space is still missing. In this work, we introduce metrics for comparing the performance and area efficiency of ring oscillators and a methodology for determining these metrics. As a result, we present a systematic study of the design space for ring oscillators for a Xilinx Virtex-5 platform FPGA.

Programming and Scheduling Model for Supporting Heterogeneous Accelerators in Linux - Beisel, Tobias; Wiersema, Tobias; Plessl, Christian; Brinkmann, André (Proc. Workshop on Computer Architecture and Operating System Co-design (CAOS))
Keywords: funding-enhance

On the Feasibility and Limitations of Just-In-Time Instruction Set Extension for FPGA-based Reconfigurable Processors - Grad, Mariusz; Plessl, Christian (Int. Journal of Reconfigurable Computing (IJRC))

Über die Rechtfertigung wirtschaftlichen Handelns. CO2-Handel in der kommunalen Energiewirtschaft - Knoll, Lisa

Individuelle Förderung in der fachdidaktischen Physiklehrerausbildung - Jonas-Ahrend, Gabriela
In der universitären Lehrerausbildung spielt die fachdidaktische Ausbildung im Vergleich zur fachlichen i.d.R. nur eine untergeordnete Rolle. Um so wichtiger ist es, die fachdidaktischen Elemente effektiv zu gestalten und auch dort Elemente individueller Förderung aufzunehmen. Im Schülerwettbewerb „virtual science fair“ werden Lehramtsstudierende als „E-Mentoren“ eingesetzt. Jedem Schülerteam wird ein E-Mentor zugeteilt, mit dem es sein Projekt plant und auswertet. Die Diskussion erfolgt ausschließlich über die Arbeitsplattform "moodle". Dadurch ist der gesamte Kommunikationsprozess Schülerteam – Student/Studentin in schriftlicher Form vorhanden und bildet eine ideale Basis, um mit den Studierenden ihre Dialoge mit ihren Schülerteams umfassend aus fachdidaktischer Sicht zu analysieren. Diese (in zweifacher Hinsicht) individuelle Förderung ist eine nützliche, innovative Facette in der fachdidaktischen Lehrerausbildung. Es hat sich zudem gezeigt, dass die Studierenden ein großes Verantwortungsgefühl für ihr Team entwickeln und mit großem Engagement bei diesem realen Projekt dabei sind

Verbesserung des Schülerinteresses selbstverständlich? - Wlotzka, Udo; Jonas-Ahrend, Gabriela
Die Kontextorientierung im Physikunterricht wird weitgehend uneingeschränkt als eine Möglichkeit der Verbesserung des Physikunterrichts gesehen. Nahezu übereinstimmend belegen alle empirischen Studien, dass kontextorientierter Unterricht positiven Einfluss auf das Interesse der Schülerinnen und Schüler hat. Im Lehrerfortbildungsprojekt „piko-DO“ wurde zum Inhaltsfeld „Elektrizität“ eine kontext- und schülerorientierte Unterrichtseinheit „Mein elektrifiziertes Jugendzimmer“ entwickelt, von verschiedenen Lehrkräften im Unterricht eingesetzt und evaluiert. Die Auswertung der Schülerfragebögen führte zu dem sowohl überraschenden als auch ernüchternden Ergebnis, dass sich das Interesse der Schülerinnen und Schüler kaum verändert hat. Im Vortrag werden die Unterrichtsreihe und einige Ergebnisse der Fragebogenuntersuchung dargestellt und in Zusammenhang mit Aussagen aus Interviews mit den unterrichtenden Lehrkräften und in Bezug zu bisherigen empirisc

Handbuch Mediologie. Signaturen des Medialen

Börsencharts im Fernsehen: Beobachtungsinstrumente des Finanzmarktes und seiner Krisen - Bartz, Christina (Krise, Cash & Kommunikation. Die Finanzkrise in den Medien)

Einleitung – Signaturen des Medialen - Bartz, Christina (Handbuch Mediologie. Signaturen des Medialen)

Medienereignis - Bartz, Christina (Handbuch Mediologie. Signaturen des Medialen)

ECR-Ectching of Submicron and Nanometer Sized 3C-SiC(100) Mesa Structures - Hiller, Lars; Stauden, Thomas; Kemper, Ricarda M.; Lindner, Jörg; As, Donat J.; Pezoldt, Jörg (Materials Science Forum)
Anisotropic etching processes for mesa structure formation using fluorinated plasma atmospheres in an electron cyclotron resonance (ECR) plasma etcher were studied on Novasic substrates with 10 μm thick 3C-SiC(100) grown on Si(100). To achieve reasonable etching rates, a special gas inlet system suitable for injecting SF6 into the high density downstream Ar ECR plasma was designed. The influence of the etching mask material on the sidewall morphology was investigated. Masking materials with small grain sizes are preferable to achieve a desired shape. The evolution of the mesa form was investigated in dependence on the gas composition, the applied bias, the pressure and the composition of the gas atmosphere. The achieved sidewall slope was 84.5 deg. The aspect ratios of the fabricated structures in the developed residue free ECR plasma etching process were between 5 and 10. Mesa structures aligned to [100] and [110] directions were fabricated.

Akzeptierte grammatische Abweichung und stilistischer Kunstgriff. Eine kleine Kommunikationsgeschichte der Ausklammerung - Schuster, Britt-Marie (Bergwerk der Sprache. Eine Geschichte des Deutschen in Episoden)
Keywords: Kommunikationsgeschichte

Andersschreiben: Formen, Funktionen, Traditionen - Schuster, Britt-Marie; Tophinke, Doris
Keywords: Textsortengeschichte

Cepat Bicara Bahasa Jerman Sehari-hari - Kilsbach, Sebastian; Pujiastuti, Suci
Lehrwerk Deutsch-Indonesisch

Microphone Array Position Self-Calibration from Reverberant Speech Input - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (International Workshop on Acoustic Signal Enhancement (IWAENC 2012))
In this paper we propose an approach to retrieve the geometry of an acoustic sensor network consisting of spatially distributed microphone arrays from unconstrained speech input. The calibration relies on Direction of Arrival (DoA) measurements which do not require a clock synchronization among the sensor nodes. The calibration problem is formulated as a cost function optimization task, which minimizes the squared differences between measured and predicted observations and additionally avoids the existence of minima that correspond to mirrored versions of the actual sensor orientations. Further, outlier measurements caused by reverberation are mitigated by a Random Sample Consensus (RANSAC) approach. The experimental results show a mean positioning error of at most 25 cm even in highly reverberant environments.
Keywords: Unsupervised; geometry calibration; microphone arrays; position self-calibration

Smartphone-Based Sensor Fusion for Improved Vehicular Navigation - Walter, Oliver; Schmalenstroeer, Joerg; Engler, Andreas; Haeb-Umbach, Reinhold (9th Workshop on Positioning Navigation and Communication (WPNC 2012))
In this paper we present a system for car navigation by fusing sensor data on an Android smartphone. The key idea is to use both the internal sensors of the smartphone (e.g., gyroscope) and sensor data from the car (e.g., speed information) to support navigation via GPS. To this end we employ a CAN-Bus-to-Bluetooth adapter to establish a wireless connection between the smartphone and the CAN-Bus of the car. On the smartphone a strapdown algorithm and an error-state Kalman filter are used to fuse the different sensor data streams. The experimental results show that the system is able to maintain higher positioning accuracy during GPS dropouts, thus improving the availability and reliability, compared to GPS-only solutions.
Keywords: Smartphone; navigation; sensor fusion

Event Processing for Intelligent Resource Management Including Prestigious Applications of Artificial Intelligence - Artikis, Alexander; Marterer, Robin; Pottebaum, Jens; Paliouras, Georgios (ECAI 2012 - 20th European Conference on Artificial Intelligence. Including Prestigious Applications of Artificial Intelligence (PAIS-2012) System Demonstrations Track, Montpellier, France, August 27-31 , 2012)
Keywords: Ver{\

User-Oriented Evaluation of Event-Based Decision Spport Systems - Pottebaum, Jens; Artikis, Alexander; Marterer, Robin; Paliouras, George (IEEE 24th International Conference on Tools with Artificial Intelligence)
Keywords: Ver{\

Event Processing for Intelligent Resource Management - Artikis, Alexander; Marterer, Robin; Pottebaum, Jens; Paliouras, Georgios (Proceedings of the 20th European Conference on Artificial Intelligence)
The need for intelligent resource management (IRM) spans across a multitude of applications. To address this requirement, we present EP-IRM, an event processing system recognising composite events given multiple sources of information in order to support IRM. EP-IRM has been deployed in two real-world applications. Moreover, with a small effort it may be used in a wide range of applications requiring IRM. We present an evaluation of the system, and discuss the lessons learnt during its development and deployment.

W. Kühlmann (Hg.): Reuchlins Freunde und Gegner. Kommunikative Konstellationen eines frühneuzeitlichen Medienereignisses. Tübingen 2010 - Moritz, Tilman (H-Soz-Kult)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

„Die Frau, die Reportage macht“ – Zu einigen Elementen des Schreibstils von Journalistinnen der 1920er Jahre - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs X. Texte – Zeugnisse des produktiven Sprachhandelns von Frauen in privaten, halböffentlichen und öffentlichen Diskursen vom Mittelalter bis in die Gegenwart. Internationale Fachtagung Paderborn 04. – 07.09.2011)
Keywords: Historische Medienlinguistik

Eine "Balancierstange": Fremdwortgebrauch und Identitätskonstruktion in den Tagebüchern Victor Klemperers - Schuster, Britt-Marie (Vielheit und Einheit der Germanistik weltweit. Akten des XII. Internationalen Germanistenkongresses Warschau 2010 (Publikationen der Internationalen Vereinigung für Germanistik))
Keywords: Kommunikationsgeschichte

Anders denken – anders schreiben. Überlegungen zur linguistischen Textanalyse am Beispiel des Essays - Schuster, Britt-Marie (Andersschreiben: Formen, Funktionen, Traditionen)
Keywords: Textsortengeschichte

Textlinguistik - Schuster, Britt-Marie (Kanzleisprachenforschung. Ein internationales Handbuch)
Keywords: Textsortengeschichte

Andersschreiben. Formen, Funktionen, Traditionen
Keywords: Textsortengeschichte